ENT 530 Social Media Portfolio / Nurul Nadiah Kamisan - Kamisan, Nurul Nadiah (2019)
Nady Nady Bakery (NNB) offers some kind of sweets that are chocolate moist cake, brownies, chocolate cheese lava berhantu cake, chocolate chip cookies and cheese tart blueberry.